Local Wisdom Based Da’wah in the Oral Tradition of the Jambi Malay Seloko Adat - Sihabudin Noor (Ilmu Dakwah: Academic Journal for Homiletic Studies, 2019)
On its arrival in Jambi, Islam had interacted with the indigenous culture. Through pacifique penetration, Islam influenced local society and socio-cultural institutions. Islam used the traditional poem of seloka which is a form of the Malay spoken literature as a medium to spread out the Islamic values and thoughts. Islam even became the main source in establishing the Jambi's local culture and wisdom. The study explains da’wah in local wisdom of traditional poem of seloka (seloko, Jambinese) Jambi Malay.  Using qualitative method by reading and learning the main research sources of descriptive data which were manuscripts of traditional poem of seloka. Interview with resource persons who were competent on content and value of the poems were also conducted to enhanche the  interpretation on data. The  conclusion of the study finds that the da’wah movement based on local wisdom brought about tightly bound relation between Islam and Jambi Malay Culture; Islamic value were modified into traditional law that commonly use seloka. The reality shows there is harmony between  the local culture and the Quran  and Sunnah.      Islam mempengaruhi masyarakat dan institusi sosial-budaya setempat. Dengan memanfaatkan seloko adat yang merupakan salah satu bentuk sastera lisan Melayu, bahasa sastera ini menjadi alat penyemai nilai dan ajaran Islam, sehingga pada akhirnya agama ini menjadi sumber utama bagi pembentukan adat dan kearifan lokal. Artikel ini menjelaskan dakwah dalam kearifan lokal seloko adat Melayu Jambi. Islam sejak awal kedatangannya telah berinteraksi dengan budaya setempat. Lewat penetrasi damai (pacifique penetration), Menggunakan metode kualitatif, penelitian ini berupaya mempelajari dan memahami naskah seloko adat dan kaitannya dengan kearifan lokal dan dakwah Islam. Wawancara ke beberapa tokoh penting dilakukan sebagai bagian dari pengayaan data untuk memahami  lebih lanjut mengenai isi dan nilai seloko. Kajian ini menyimpulkan bahwa akibat adanya gerakan dakwah yang berkearifan lokal dalam budaya Melayu Jambi terdapat hubungan yang erat antara Islam dan budaya masyarakat melayu Jambi; seperti  adanya modifikasi nilai-nilai Islam ke dalam hukum adat yang umumnya menggunakan bahasa seloko. Realitas itu menunjukan adanya harmoni antara budaya lokal dengan Alquran dan Sunnah Rasul.